THE COMPARISON ON THE USE OF TRADITIONAL AND AUTHENTIC ASSESSMENT IN ELT - Wawat Srinawati; Nadiva Rahma Mira (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
The purpose of this research is to investigate assessment practices in English learning classes at junior high school, particularly in education, and to know what kinds of assessments are often used by English teachers. This study use a qualitative descriptive method using observation and interviews. The object ofthis research was three English teachers who teach English at SMP Negeri 4 Leuwiliang. Therefore, the writer hopes this research give helpful information for anyone directly or indirectly related to education. The results show that traditionaland alternative are used to measure different types of abilities, and at this time teachers are still dominant in using traditional assessments, because they areeasier to use than authentic assessments which require more time and accuracy.